2011
DOI: 10.1155/2011/659704
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of Essential Oil from the Seed of Anethum graveolens L. against Candida spp.

Abstract: The essential oil produced from the seed of Anethum graveolens L. (Umbelliferae) was tested in vitro and in vivo anti-Candida activity. The microbroth dilution method was used in the minimal inhibitory concentration (MIC), according to M27-A3 of the guidelines of the Clinical and Laboratory Standard Institute (CLSI). And then, efficacy evaluation of essential oil in the prophylaxis and treatment of experimental vaginal candidiasis was performed in immunosuppressed mice. The anti-Candida activity was analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…In the chromatography analysis of the essential oil of A. graveolens, the principal identified constituents were Carvone, Apiol, D-limonene, Dihydrocarvone and Trans-dihydrocarvone agreeing with the studies by Zeng et al (2011);Tian et al (2011), featuring the carvone, limonene and apiol as the majority compounds.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the chromatography analysis of the essential oil of A. graveolens, the principal identified constituents were Carvone, Apiol, D-limonene, Dihydrocarvone and Trans-dihydrocarvone agreeing with the studies by Zeng et al (2011);Tian et al (2011), featuring the carvone, limonene and apiol as the majority compounds.…”
Section: Discussionsupporting
confidence: 80%
“…clinical isolates. In the study by Zeng et al (2011), using the broth microdilution technic (MIC), microbiological and histological technics in mice, demonstrated that dill was active in vitro and in vivo against all the Candida species tested. Yili et al (2009), analyzed the MIC through the Barry method, with an ethylene oxide addition, and they found inhibition results of 0.00273 mg.mL -1 in C. albicans, affirming that the yeast growth, sharply decreased with this component addition in the nutrient medium.…”
Section: Discussionmentioning
confidence: 99%
“…Oral candidiasis is normally treated with antifungal agents such as nystatin, miconazole, fluconazole, itraconazole, imidazole, triazole and amphotericin B. However, occasional consumption of the effective dose cannot be tolerated due to side effects [7,8]. In addition, these agents may induce antifungal resistance in C. albicans [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Etarsko ulje ploda mirođije deluje antifungalno na soj Candida albicans [59], kao i na Aspergillus flavus [60], tako što pogađa citoplazmatičnu membranu i mitohondrije ovih gljiva [60,61]. Etarsko ulje ploda mirođije inhibira i rast A. niger i Sacharomyces cerevisae [62].…”
Section: Antimikrobno Dejstvounclassified